Pedagogical practices, personal learning environments and the future of eLearning - Páscoa, Rui (2020)
Historically, elearning has adopted the most common pedagogical models in Distance Education and it has been gaining increasing importance, as Higher Education Institutions are offering more and more online degrees. However there is a gap between theory and practice. What are the actual pedagogical models followed by the teachers online? Do they follow the theoretical models or do they adopt a mix of different models? What is the role of the services and tools available in the pedagogical practices, namely the Personal Learning Environments (PLEs)? How are Higher Education Institutions adapting themselves and which are the future trends for elearning? This paper tries to shed some light on these questions based on two interviews: one to Prof. Graham Attwell and the other to Prof. José Lagarto. Showing some skepticism about the adoption of elearning by Universities, the interviewees consider that PLEs are indeed capable of bringing a quality increase in the learning process. They also consider it is necessary to adopt several pedagogical models in elearning.